Nuclear reprocessing-related radiocarbon (14C) uptake into UK marine mammals. Issue 1 (15th November 2017) - Tierney, Kieran M.; Muir, Graham K.P.; Cook, Gordon T.; Heymans, Johanna J.; MacKinnon, Gillian; Howe, John A.; Xu, Sheng; Brownlow, Andrew; Davison, Nicholas J.; ten Doeschate, Mariel; Deaville, Rob
Abstract: To evaluate the transfer of Sellafield-derived radiocarbon ( 14 C) to top predators in the UK marine environment, 14 C activities were examined in stranded marine mammals. All samples of harbour porpoise ( Phocoena phocoena ) obtained from the Irish Sea showed 14 C enrichment above background. Mammal samples obtained from the West of Scotland, including harbour porpoise, grey seals ( Halichoerus grypus ) and harbour seals ( Phoca vitulina ) showed 14 C enrichment but to a lesser extent. This study demonstrates, for the first time, enriched 14 C is transferred through the marine food web to apex predators as a consequence of ongoing nuclear reprocessing activities at Sellafield. Total Sellafield 14 C discharge activity 24 months prior to stranding and, in particular, distance of animal stranding site from Sellafield are significant variables affecting individual 14 C activity. 14 C activities of West of Scotland harbour porpoises suggest they did not forage in the Irish Sea prior to stranding, indicating a high foraging fidelity. Highlights: Enriched 14 C activities found in Irish Sea harbour porpoises. Enriched 14 C activities found in West of Scotland porpoises and seals. Distance from Sellafield correlates significantly with sample activity. Sellafield 14 C discharges correlates significantly with sample activity.